Dukungan Penampilan Guru Dalam Pembelajaran, Motivasi, Dan Fasilitas Terhadap Kedisiplinan Belajar Dan Dampaknya Pada Hasil Belajar Matematika Siswa Kelas VII SMP Negeri 6 Salatiga Tahun Ajaran 2016/2017 Tahun Ajaran 2016/2017 - Janah, Nugraheni Nur, Prof. Dr. Sutama, M.Pd (2017)
Nugraheni Nur Janah/ A410130053. Support of the teacher's appearance in the learning, motivation, and facilities through discipline learning and the impact on learning outcomes for mathematics students of VII grade Junior High School of 6 Salatiga in academic year 2016/2017. Research of paper. Faculty of Teaching and Education Training. Muhammadiyah University of Surakarta. June, 2017. Mathematics learning outcomes is important in the learning process to determine the level of students understanding of the material being studies in learning. The learning result is a result of the learning is non-physical activities such as changes in attitudes, knowledge, and prowess. The purpose in this study are to examine. 1) Contribution of the teacher's appearance in the learning, motivation, and facilities towards mathematics learning outcomes inderectly through discipline learning; 2) Contribution of the teacher's appearance in the learning, motivation and facilities towards discipline learning; 3) Contribution of discipline learning towards mathematics learning outcomes. The type of this study is correlation using a quantitative approach. Population in this study as many as 190 students. Sampling technique using proportional random sampling by lottery. The number of samples in this study are 128 students. Data collection techniques using method of documentation and questionnaire. Data analysis technique using path analysis.Result of student data junior high school 6 Salatiga by categoris of high, medium, low tend to have mathematics learning outcomes in the medium category with a percentage of 64.06% or 82 students out of 128 samples. Discipline learning in the medium category with a percentage of 68.75% or 88 students out of 128 samples. Teacher's appearance in the learning in the medium category with percentage of 75% or 96 students out of 128 samples. Motivation in the medium category with percentage of 68.75 or 88 students out of 128 samples. Facilities in the medium category with percentage of 64.84% or 83 students out of 128 samples. This result indicate that. 1) There is a contribution of the teacher's appearance in the learning, motivation, and facilities and significant impact on mathematics learning outcome indirectly through discipline learning, with the contribute of 10%; 2) There is a contribution of the teacher's appearance in the learning, motivation, facilities and significant impact on dicipline learning, with the contribution of 22.1%; 3) There is a contribution of dicipline learning and significant impact on mathematics learning outcomes, with the contribution of 4.16%. Keyword: teacher's appearance, motivation, facilities, discipline learning, learning outcomes